A Sectoral Analysis of Price-Setting Behavior in US Manufacturing Industries - Campbell Leith; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we develop a multi-sector model of firms' pricing behaviour under imperfect competition. We allow for the fact that some goods sold will be for final consumption, while others will be used as intermediate goods in further production. We assume that price setters are constrained by the existence of Calvo (1983) contracts which enables us to measure the extent of price inertia across industrial sectors. We further allow for the possibility that some firms set prices to maximise the discounted value of profits, while others set prices according to a backward-looking rule-ofthumb. We then estimate the resulting price-setting equations for 18 US manufacturing industries defined at the SIC 2-digit level over the period 1959 to 1996. We find that there is statistically significant variability in estimates of price stickiness, ranging from 4 months to almost 1.5 years with significantly more inertia in the setting of durable goods prices. We also find that estimates of backward-looking price-setting behaviour vary, with some industries acting in a purely forward-looking manner, while others are characterized by almost 50 per cent of firms setting prices in a backwardlooking fashion. Finally we find that firms in less competitive industries (characterized by higher average markup-ups) tend to adjust prices less frequently and are less likely to do so in a forward-looking manner.
Keywords: 330